κ-Carrageenan/Sodium Alginate: A New Synthesis Route and Rapid Adsorbent for Hydroxychloroquine Drug - Mohammed Kassim Al-Hussainawy; Layth Sameer Al-Hayder (Indonesian Journal of Chemistry, 2023)
In recent years, the huge amounts of chemicals that are used as drugs and their derivatives have been exposed to the environment due to the COVID-19 pandemic. Some of these drugs (i.e. hydroxychloroquine (HCQ)) have a serious risk on aquatic media. In this study, carrageenan/sodium alginate (κC/Sa) was investigated as a biopolymer, environmentally friendly, and rapidly adsorbent to eliminate HCQ from its aqueous solution. The biopolymer (κC/Sa) was synthesized by free radical polymerization assisted by ultrasound in the presence of acrylic acid as cross-linkage and potassium persulfate as an initiator. The natural κC/Sa was characterized by FTIR, XRD, BET, BJH, and SEM techniques. The produced co-polymer had a mesoporous surface with high purity and significant thermal stability. The best parameters were determined to be 0.05 g biopolymer, 200 ppm initial HCQ concentration, salts, and pH = 7. The adsorption mechanism follows a pseudo second-order kinetic model, and the adsorption isotherm follows a Freundlich model, with qe reaching 89.8 mg/g at 500 ppm HCQ. Thermodynamic studies indicated that the adsorption of hydroxychloroquine drugs was an exothermic spontaneous process.